2017
DOI: 10.4338/aci-2016-10-ra-0176
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electronic Algorithms to Improve Diagnostic Evaluation for Bladder Cancer

Abstract: Triggers offer a promising method to detect delays in care of patients with high-grade hematuria and warrant further evaluation in clinical practice as a means to reduce delays in bladder cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Definitions of timely evaluation, referral and diagnosis, were described in 12 studies. For time to first evaluation including cystoscopy, upper urinary tract imaging or urine cytology, Garg et al used a threshold of 30 days,32 while two studies examined proportions of patients undergoing these tests within 6033 and 90 days 24. The remaining studies used 180 days as time cut-offs for which they considered evaluation should be carried out,22 28 34–36 although one also looked at completion within 365 years, and beyond 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Definitions of timely evaluation, referral and diagnosis, were described in 12 studies. For time to first evaluation including cystoscopy, upper urinary tract imaging or urine cytology, Garg et al used a threshold of 30 days,32 while two studies examined proportions of patients undergoing these tests within 6033 and 90 days 24. The remaining studies used 180 days as time cut-offs for which they considered evaluation should be carried out,22 28 34–36 although one also looked at completion within 365 years, and beyond 28.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported the frequency of appropriate or guideline-concordant diagnostic tests and referrals performed during diagnostic evaluation (online supplementary appendix 2). Studies examining the frequency of non-evaluation of haematuria reported this to be 47%–81% within 60 days of initial symptom presentation,24 33 reducing to 36%–65% in studies by 180 days 22 34–36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations